Sexual Function and Its Relationship to Quality of Life among Married Women - Mareti, Silvia; Afiyanti, Yati; Budiati, Tri (Universitas Ahmad Dahlan, 2025)
Sexual function is one of the key elements of women's quality of life, reflecting their biological, emotional, and social well-being. This cross sectional study aims to identify the relationship between sexual function and women's quality of life. Method: Sampling used proportions according to the inclusion criteria with 305 female participant of productive age in DKI Jakarta Province. Significant relationships between sexual desire p = 0.00 and r = -.19, lubrication p = 0.00 and r = 0.17 and physical health domains, all with weak relationship strength. A significant relationship is also observed between sexual satisfaction p = 0.01 and r = 0.14 and the psychological domain, with weak relationship strength. Additionally, there is a significant relationship between sexual arousal p = 0.00 and r = 0.30, lubrication p = 0.00 and r = 0.27, and social relationship domains, with moderate relationship strength. A significant relationship exists between orgasm p = 0.00 and r = 0.19, sexual satisfaction p = 0.00 and r = 0.34 and the social relationship domain, with weak relationship strength. Considering the critical impact of sexual function on the health of couples, it is important to pay attention to sexual function in women. Therefore, there is a need for sexual health assessments and the design of educational programs to improve their quality of life.